Deciphering the extreme X-ray variability of the nuclear transient eRASSt J045650.3-203750: A likely repeating partial tidal disruption event - Liu, Z.; Malyali, A.; Krumpe, M.; Homan, D.; Goodwin, Adelle; Grotova, I.; Kawka, A.; Rau, A.; Merloni, A.; Anderson, Gemma; Miller-Jones, James; Markowitz, A.G.; et al. (EDP SCIENCES S A, 2023)
Context. During its all-sky survey, the extended ROentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spectrum-Roentgen-Gamma (SRG) observatory has uncovered a growing number of X-ray transients associated with the nuclei of quiescent galaxies. Benefitting from its large field of view and excellent sensitivity, the eROSITA window into time-domain X-ray astrophysics yields a valuable sample of X-ray selected nuclear transients. Multi-wavelength follow-up enables us to gain new insights into understanding the nature and emission mechanism of these phenomena. Aims. We present the results of a detailed multi-wavelength analysis of an exceptional repeating X-ray nuclear transient, eRASSt J045650.3-203750 (hereafter J0456-20), uncovered by SRG/eROSITA in a quiescent galaxy at a redshift of z ∼ 0:077. We aim to understand the radiation mechanism at different luminosity states of J0456-20, and provide further evidence that similar accretion processes are at work for black hole accretion systems at different black hole mass scales. Methods. We describe our temporal analysis, which addressed both the long- and short-term variability of J0456-20. A detailed X-ray spectral analysis was performed to investigate the X-ray emission mechanism. Results. Our main findings are that (1) J0456-20 cycles through four distinctive phases defined based on its X-ray variability: an X-ray rising phase leading to an X-ray plateau phase that lasts for abouttwo months. This is terminated by a rapid X-ray flux drop phase during which the X-ray flux can drop drastically by more than a factor of 100 within one week, followed by an X-ray faint state for about two months before the X-ray rising phase starts again. (2) The X-ray spectra are generally soft in the rising phase, with a photon index & 3:0, and they become harder as the X-ray flux increases. There is evidence of a multi-colour disk with a temperature of Tin ∼ 70 eV in the inner region at the beginning of the X-ray rising phase. The high-quality XMM-Newton data suggest that a warm and hot corona might cause the X-ray emission through inverse Comptonisation of soft disk seed photons during the plateau phase and at the bright end of the rising phase. (3) J0456-20 shows only moderate UV variability and no significant optical variability above the host galaxy level. Optical spectra taken at different X-ray phases are constant in time and consistent with a typical quiescent galaxy with no indication of emission lines. (4) Radio emission is (as yet) only detected in the X-ray plateau phase and rapidly declines on a timescale of two weeks. Conclusions. J0456-20 is likely a repeating nuclear transient with a tentative recurrence time of ∼223 days. It is a new member of this rare class. We discuss several possibilities to explain the observational properties of J0456-20. We currently favour a repeating partial tidal disruption event as the most likely scenario. The long-term X-ray evolution is explained as a transition between a thermal disk-dominated soft state and a steep power-law state. This implies that the corona can be formed within a few months and is destroyed within a few weeks.